LEARNING ENGLISH IN NON-FORMAL EDUCATION IN INDONESIA: A LITERATURE REVIEW - Siska Tasdin; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
The study's goal was to critically examine the practice of foreign language, particularly English, which was largely underpaid for the cultural accretion that came with it, and to find ways to raise awareness of English's importance without eradicating cultural norms, resulting in a society of good character. They also help us understand how we can improve our national competitiveness in the face of globalization, where English is the language of unity or regional language. The author hopes that readers will be able to understand our own foreign and cultural cultures, particularly in Indonesia, through English studies to support character education.